The legitimacy of the African Court on Human and Peoples’ Rights after the withdrawal of Rwanda, Tanzania, Benin, and Côte d’Ivoire from Article 34(6) of the Protocol to the African Charter on Human and Peoples’ Rights on the Establishment of an African Court on Human and Peoples’ Rights - De Klerk, Derick Ras (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLM)--Stellenbosch University, 2023.